The impact of the Restrictive Practices (Groceries) Order on competition in the Irish grocery trade - Donnelly, Gerry (Statistical and Social Inquiry Society of Ireland, 2006)
This paper analyses the history and key provisions of the Restrictive Practices (Groceries Order) since its inception in 1956 and demonstrates how the most recent incarnation of the Order in 1987 was fundamentally different from its predecessors. The Paper concludes that the provisions of the 1987 Order were self-defeating and contradictory, and, because they re-introduced a form of resale price maintenance into the grocery trade, represented a reversal of Government policy of the previous 30 years and served only to encourage rather than prevent anti-competitive pricing. Statistical and economic evidence is used to demonstrate how the Order eliminated price competition from the trade and encouraged vertical integration between suppliers and retailers that resulted in increased market concentration. In this way, the paper establishes a chain of cause and effect between the Order and higher grocery prices in Ireland. The evidence also points to the fact that the Order was incapable of achieving any of its stated objectives ? including those of protecting suppliers from the buying power of large multiple retailers and guaranteeing the continued existence of small independent grocers. The conclusion is drawn, based on an analysis of market trends and structures, that the Irish grocery trade is segmented in two niche markets serving respectively the convenience and ?one-stop? customer and that there is no reason to believe that revoking the Order will damage competition or result in any consumer detriment.
Read before the Society, 23 March 2006
Keywords: Competition; Restrictive practices; Grocery trade; Pricing; 314.15